Alteration of T cell maturation and proliferation in the mouse thymus induced by serum factors from patients with ulcerative colitis. - Watanabe, M (1987)
Recently it has been reported that patients with ulcerative colitis (UC) often have thymus abnormalities, although the precise mechanisms which induce those abnormalities remain unclear. We have examined the effect of serum fractions from patients with UC and other colonic diseases on mouse thymus to clarify the possible existence of factors which have thymus growth activity. These fractions were separated from sera of patients with UC by gel filtration and anion exchange high performance liquid chromatography. In mice given UC serum fractions; (i) remarkable increases in weight and total cell number of the thymus were observed from day 4 to day 9; (ii) a significant increase in the number of peanut agglutinin (PNA)+ thymus cells was demonstrated using flow cytometry on day 9; (iii) on quantitative analysis of surface antigens the percentage of Lyt-2+ thymus cells decreased and that of L3T4+ thymus cells increased remarkably on day 13; the number of bright Thy-1.2+ cells and of dull Lyt-1+ cells increased. In contrast, the serum fractions from patients with other colonic diseases and from normal persons caused little change in mouse thymus throughout the study. The results suggest that factors fractionated from the serum of patients with UC disturb intra-thymic T cell maturation and enhance the proliferation of thymus cells.